2017
DOI: 10.3389/fvets.2017.00017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visceral Fat Accumulation and Metabolome Markers among Cats of Varying BCS and Novel Classification of Feline Obesity and Metabolic Syndrome

Abstract: As in humans, obesity and its associated diseases represent the most significant threat to the health of veterinary populations. Previous human studies have provided insights into the risk factors of obesity, complex pathogenesis of obesity-associated diseases, and their life-threatening consequences. In humans, the “metabolic syndrome” represents a cluster of metabolic risk factors associated with the development of cardiovascular disease. Risk factors for metabolic syndrome, such as diabetes, obesity, high b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 64 publications
3
32
1
6
Order By: Relevance
“…In this study, high plasma TC of >180 mg/100 mL was considered as hyperlipidemia according to the criteria of metabolic syndrome in cats. 8 Based on this amended criteria, all four cats with over 180 mg/ 100 mL of plasma TC are diagnosed as obesity disease, and they were alleviated from obesity disease after quercetin derivative supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, high plasma TC of >180 mg/100 mL was considered as hyperlipidemia according to the criteria of metabolic syndrome in cats. 8 Based on this amended criteria, all four cats with over 180 mg/ 100 mL of plasma TC are diagnosed as obesity disease, and they were alleviated from obesity disease after quercetin derivative supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…18 For overweight cats with high BCS of >7/9, showing low adiponectin (<3.0 μg/mL), hyperlipidemia (triglyceride >165 mg/100mL or total cholesterol >180 mg/100mL) and high serum amyloid A concentrations (>200 ng/mL), categorized them as having obesity disease. 8,19 Informed consent was obtained from each client on the written form. The informed consent included information about possible risk, benefits, and limits of examination.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cats, atherosclerosis does not present as a clinical problem. Nevertheless, since an elevated BCS is associated with insulin resistance [13], it has been suggested that an additional classification of feline metabolic syndrome, using BCS associated with increased blood glucose, dyslipidaemia and low adiponectin [14]. However, whether such a classification has practical clinical value is yet to be determined.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…In healthy cats, nearly 40% of the variance in final body weight after 8 weeks of ad libitum feeding is explained by initial body weight, energy requirements for maintenance and fasting leptin [46]. Adiponectin has been used in a classification of feline metabolic syndrome [14]. The role of other adipokines prediction and pathogenesis of overweight and obesity requires further study.…”
Section: Endocrine Disruptors and Hormonal Influencesmentioning
confidence: 99%